Combining ability and hybrid breeding in pearl millet (Pennisetum glaucum [L.] R. Br.) for agronomic traits and resistance to Striga hermonthica - Rouamba, Armel; Hussein, Shimelis; Drabo, Inoussa; Mrema, Emmanuel; Mashilo, Jacob; Mwadzingeni, Learnmore (Springer, 2024)
Pearl millet (Pennisetum glaucum [L.] R. Br., 2n = 2x = 14) is a nutrient-dense and climate-resilient crop widely cultivated in the dry regions of Africa and Asia. In Burkina Faso, the actual mean yield of the crop is < 1 ton/ha compared with a potential yield of 3 tons/ha. Several constraints, including cultivar susceptibility to the noxious weed Striga hermonthica (Del.) Bentham (Sh) and severe and recurrent drought stress limit the potential productivity of the crop. Therefore, this study aimed to determine the combining ability effects and degree of heterosis for agronomic traits and resistance to Sh among complementary pearl millet genotypes to select promising parental lines and hybrids to develop and deploy farmer-preferred varieties. The narrow-and broad-sense heritability were relatively higher for Striga-resistance (>= 70%) and low (<= 23%) for grain yield. The general combining ability and specific combining ability ratios were less than unity for agronomic traits and Striga reaction indicating the predominance of non-additive gene action conditioning the assessed traits. The new experimental hybrids such as IP-11358 x ICMB177111, IP-11358 x IKMB18002, IP-10579 x ICMB177002 and IP-9242 x ICMB177002 are recommended for multi-environment evaluation and production in Sh-infested pearl millet cultivation agro-ecologies in Burkina Faso or similar agro-ecologies.